Diagnostic accuracy of SARS-CoV-2 rapid antigen test from self-collected anterior nasal swabs in children compared to rapid antigen test and RT-PCR from nasopharyngeal swabs collected by healthcare workers: A multicentric prospective study - Cohen, Robert; Aupiais, Camille; Filleron, Anne; Cahn-Sellem, Fabienne; Romain, Olivier; Béchet, Stéphane; Auvrignon, Anne; Batard, Christophe; Virey, Brigitte; Jung, Camille; Rybak, Alexis; Levy, Corinne (Frontiers in Pediatrics, 2022)
Testing for SARS-CoV-2 is central to COVID-19 management. Rapid antigen test from self-collected anterior nasal swabs (SCANS-RAT) are often used in children but their performance have not been assessed in real-life in children. We aimed to compare this testing method to the two methods usually used: reverse transcription polymerase chain reaction from nasopharyngeal swabs collected by healthcare workers (HCW-PCR) and rapid antigen test from nasopharyngeal swabs collected by healthcare workers (HCW-RAT) in children, estimating the accuracy and acceptance, in a pediatric real-life study. From September 2021 to January 2022, we performed a manufacturer-independent cross-sectional, prospective, multicenter study involving 74 pediatric ambulatory centers and 5 emergency units throughout France. Children ≥6 months to 15 years old with suggestive symptoms of COVID-19 or children in contact with a COVID-19–positive patient were prospectively enrolled. We included 836 children (median 4 years), 774 (92.6%) were symptomatic. The comparators were HCW-PCR for 267 children, and HCW-RAT for 593 children. The sensitivity of the SCANS-RAT test compared to HCW-RAT was 91.3% [95%CI 82.8;96.4]. Sensitivity was 70.4% [95%CI 59.2;80.0] compared to all HCW-PCR and 84.6% [95%CI 71.9;93.1] when considering cycle threshold <33. The specificity was always >97%. Among children aged ≥6 years, 90.9% of SCANS-RAT were self-collected without adult intervention. On appreciation rating (from 1, very pleasant, to 10, very unpleasant), 77.9% of children chose a score ≤3. SCANS-RAT have good sensitivity and specificity and are well accepted by children. A repeated screening strategy using these tests can play a major role in controlling the pandemic.